Agronomic Performance of F3 Populations of Tomato for Hydroponic Cultivation at Lowland Greenhouse - Febriani, Nur Futri Salsabilla; Lestari, Resti; Widiyanto, Sigit; Daryanto, Ady (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Tomatoes consumption continues to increase, but it’s constrained by low productivity in central production, so a plant breeding program is needed to improve the yield and adaptability of tomatoes in urban areas. This study aimed to analyze the agronomic performance of F3 tomato populations for hydroponic cultivation in a lowland greenhouse. The F3 populations derived from crosses of commercial variety Rewako x Tantyna (Rw.Ta-4-7U, w.Ta-4-10U, and Rw.Ta-1-14U) and Agatha x Ultima (Ag.Ul-5-7U & Ag.Ul-5-14U). The research was conducted at the Gunadarma University’s experimental greenhouse in Depok City, West Java, from March to August 2020. Twenty-fifth-day-old seedlings from each population were planted in a planter bag. The experiment was carried out using a single plant design for F3 generation and a randomized complete block design (RCBD) for the commercial varieties. The result showed that a number of fruit per plant, and fruit weight per plant had wide genetic variabilities among F3 populations. All characters had a high broad-sense heritability except for flowering days and harvesting days. The high advance genetic, along with high mean values, was shown by the F3 populations of Rw.Ta-4-10U, Rw.Ta-4-7U and Ag.Ul-5-14U. The high value of genetic variability, heritability, and genetic advance will help to select the program for the next generation.